2019
DOI: 10.3390/publications7020032
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Production and Productivity for Characterizing an Author’s Publication History: Simple and Nested Gini’s and Hirsch’s Indexes Combined

Abstract: In this study, I developed operational versions of Gini’s and Hirsch’s indexes that can be applied to characterize each researcher’s publication history (PH) as heterodox, orthodox, and interdisciplinary. In addition, the new indicators warn against anomalies that potentially arise from tactical or opportunistic citation and publication behaviors by authors and editors, and can be calculated from readily available information. I split the original Hirsch index into nested indexes to isolate networking activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 92 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…To the best of our knowledge, few papers (e.g., [1,2]) suggest an index to evaluate interdisciplinary CVs (i.e., authors applying usual methodologies to unusual topics or vice versa). In particular, Zagonari [1] identifies the interdisciplinary percentage of any CV (i.e., articles in a discipline or subject quoted by articles in different disciplines or subjects) to be applied to the H-index characterising each author, where the H-index is chosen as an easily generated quantitative index.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, few papers (e.g., [1,2]) suggest an index to evaluate interdisciplinary CVs (i.e., authors applying usual methodologies to unusual topics or vice versa). In particular, Zagonari [1] identifies the interdisciplinary percentage of any CV (i.e., articles in a discipline or subject quoted by articles in different disciplines or subjects) to be applied to the H-index characterising each author, where the H-index is chosen as an easily generated quantitative index.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, few papers (e.g., [1,2]) suggest an index to evaluate interdisciplinary CVs (i.e., authors applying usual methodologies to unusual topics or vice versa). In particular, Zagonari [1] identifies the interdisciplinary percentage of any CV (i.e., articles in a discipline or subject quoted by articles in different disciplines or subjects) to be applied to the H-index characterising each author, where the H-index is chosen as an easily generated quantitative index. However, this interdisciplinary index requires a homogeneous H-index across disciplines or subjects to avoid gains for some interdisciplinary scientists (e.g., across medicine and computing) and losses for other interdisciplinary scientists (e.g., across art and mathematics) [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that we have not included interdisciplinary research, which we define as research conducted across scientific disciplines or across artistic and scientific domains [ 8 ], since such work has been relatively scarce [ 9 ] or has been unreliably evaluated [ 10 ]; it has also been rarely funded [ 11 ]. However, Zeng et al [ 12 ] have recently shown that success in science (in terms of the average citations per paper) is negatively correlated with writing about diverse topics.…”
Section: Introductionmentioning
confidence: 99%